Screening and Identification of Thermotolerant and Osmotolerant Bacillus amyloliquefaciens BKHE Isolated from Kinema of Eastern Nepal for Alkaline Protease Production - Gyanu Raj Pandey; Asmita Shrestha; Tika B. Karki; Shardul Neupane; Sabnam Ojha; Prashanna Koirala; Parash Mani Timilsina (International Journal of Microbiology)
Alkaline protease is one of the most important industrial enzymes which are excessively used in the detergent industry, food industry, feed industry, pharmaceutical industry, leather industry, etc. 60% of the produced alkaline protease is consumed by the detergent industry alone. In the present study, bacterial isolates that can produce alkaline protease for purpose of bio-detergent were screened among the isolates isolated from kinema (an alkaline fermented food of eastern Nepal). Selected bacterial isolates were further screened for hemolysis activity and the production of other hydrolytic enzymes. Four bacterial isolates selected were tested for their capacity to produce alkaline protease in five different fermentation mediums. Isolate BKHE produces a high amount of alkaline protease (0.4705 ± 0.035 U/mL/min) in fermentation medium M2 (sucrose, 11 g/L; yeast extract, 5 g/L; and KNO3, 5.2 g/l, pH 9). The selected isolate was identified as Bacillus amyloliquefaciens BKHE based on 16S rRNA sequencing and phenotypic features. This bacterial strain was also found to be thermotolerant (confluent growth at 50°C) and salt tolerant up to 10% NaCl concentration. With its versatile ability, bacterial isolate or purified enzymes have potential applications in the food and detergent industry.